2005
DOI: 10.1002/ajim.20149
|View full text |Cite
|
Sign up to set email alerts
|

Early retirement due to occupational injury: Who is at risk?

Abstract: These factors may represent opportunities for early identification and intervention with individuals at high risk for poor post-injury outcomes. Longitudinal studies are needed to confirm the importance of these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Although the importance of matching job demand with physical ability has been hypothesized, 7,8,11,30,33 few studies have examined how occupational injury risk may be associated with a mismatch between physical ability and job demand. Our findings emphasize that in situations of high job demand for physical effort, low physical ability is associated with increased risk of occupational injury, more so than in situations when job demand and physical ability are both high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the importance of matching job demand with physical ability has been hypothesized, 7,8,11,30,33 few studies have examined how occupational injury risk may be associated with a mismatch between physical ability and job demand. Our findings emphasize that in situations of high job demand for physical effort, low physical ability is associated with increased risk of occupational injury, more so than in situations when job demand and physical ability are both high.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a 2015 study, 11% of older workers reported they intended to retire early as a consequence of prior injury. 8 Among individuals aged 51 to 61 years receiving Social Security Disability Insurance, 37% were disabled due to a workplace injury or illness. 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surveys used for this study have been described previously [21,22]. To summarize, the first survey assessed short-term outcomes as well as personal and pre-injury factors hypothesized to be associated with these outcomes including demographic information, history of prior injuries, employment history, and respondent job and industry type.…”
Section: Survey Developmentmentioning
confidence: 99%
“…An eight-item version of the Work Limitations Questionnaire was included as a measure of specific work-related functional limitation [27]. As described previously, several new items were constructed to evaluate familiarity with the task performed at the time of the injury, ease of access to medical care, and work problems encountered after the injury based on focus groups and a review of the literature [21,22]. In addition, both surveys were cognitively tested on recently injured individuals of both sexes to insure that comprehension was consistent with investigator expectations.…”
Section: Survey Developmentmentioning
confidence: 99%